Deteksi Kemacetan Lalu Lintas Melalui Kamera menggunakan Pin Hole Algorithm - Samuel Mahatmaputra; Erwin Permata; William William (Bina Nusantara University, 2011)
This paper describes the modifications to the Pinhole algorithm and applies it to the detection of highway congestion using an IP camera. This algorithm can detect the congestion on the highway with a fairly high degree of accuracy and the small possibility of false alarms, so that it helps reporting congestion and road users to take into account the best and quickest way. The methods used in this research are literature study, questionnaire analysis, and evaluation of application performance. The application made in this study can be further developed for combined detection with many cameras, and can support traffic regulation as well as SMS gateway service to check the condition of a road segment. At the end of this paper are presented techniques and methodology of determining the parameter values used in the calibration.